Enhancing Human Capital Development with Knowledge Management Strategy through Public Private Partnership - Zulfa Haitan Rachman (PT Penjaminan Infrastruktur Indonesia (Persero), 2020)
Knowledge Management uses the Nonaka’s SECI model in the creation of knowledge that can provide guidance for learning situations and activities. However, an understanding of the process of socialization, externalization, combination and internalization needs to be strengthened with extensive direct practices. Knowledge Management (KM) can accelerate joint learning to develop human capital that can enhance competitiveness and proactively respond to market changes. An understanding of knowledge management is needed to determine its influence on organizations. A systemic approach through dynamic systems can be used to determine the effect of knowledge management well and the applications of the SECI model. This study explains the use of the SECI model and dynamic system to determine the effect of knowledge management on human capital development through public private partnership. The source of knowledge provides ease to every human capital to utilize it. Thus, the process of utilizing knowledge in his environment increases, which thenpushes the process of creativity and innovation in a more broadly manner, and thus increasing competence. Identifying source and network of expertise and making expertise more visible and easily accessible ,in this case,facilitate a connection between those who possess the knowledge and those who need the knowledge.